MAT161 - Elementary Statistics February 2021 - PPSM, Pusat Pengajian Sains Matematik (Universiti Sains Malaysia, 2021)
Please check that this examination paper consists of SIX(6) pages of printed material before you begin the examination. Instructions : Answer EIGHT (8) questions.